Parents’ Interaction Styles as Perceived by Adolescents, and its Effect on their Psychological Adjustment - Rehani Sِulieman; Thweib, May; Rashdan, Izz (Jordan Journal of Educational Sciences, 2009)
This study aimed at identifying the effect of parents’ interaction styles as perceived by adolescents on their psychological adjustment. The study sample consisted of 623 students (324 females, 299 males) age between 16-17 years old. The sample was selected randomly. Both the Parents’ Interaction Styles Scale and the Psychological Adjustment Scale were used. Two- way analysis of variance was used to test the study hypotheses. The results indicate that there is a statistical significant effect of parents’ interaction styles on adolescent’s psychological adjustment, showing that positive interaction style correlates with high levels of psychological adjustment